2019
DOI: 10.1073/pnas.1812068116
|View full text |Cite
|
Sign up to set email alerts
|

Students of color show health advantages when they attend schools that emphasize the value of diversity

Abstract: As the United States becomes more diverse, the ways in which mainstream institutions recognize and address race and ethnicity will be increasingly important. Here, we show that one novel and salient characteristic of an institutional environment, that is, whether a school emphasizes the value of racial and ethnic diversity, predicts better cardiometabolic health among adolescents of color. Using a diverse sample of adolescents who attend more than 100 different schools in predominantly urban locations, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Racial equity promotion in K-12 schools is necessary and important given the systematic inequities and disparities present in the education system ( Hussar et al, 2020 , Warren, 2014 ), and in society at large ( Carter et al, 2017 , Ladson-Billings, 2006 , Webb Hooper et al, 2020 . Research shows that schools that promote more equitable practices, emphasize the value of diversity, and support culturally-relevant, school-wide mental health efforts improve the health and well-being of the student body and improve family-school partnerships ( Childs et al, 2021 , Barker et al, 2021 , Levine et al, 2019 ). Beyond this, study findings point to the importance of equitable systems for students and families across racial communities in light of the negative impacts of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Racial equity promotion in K-12 schools is necessary and important given the systematic inequities and disparities present in the education system ( Hussar et al, 2020 , Warren, 2014 ), and in society at large ( Carter et al, 2017 , Ladson-Billings, 2006 , Webb Hooper et al, 2020 . Research shows that schools that promote more equitable practices, emphasize the value of diversity, and support culturally-relevant, school-wide mental health efforts improve the health and well-being of the student body and improve family-school partnerships ( Childs et al, 2021 , Barker et al, 2021 , Levine et al, 2019 ). Beyond this, study findings point to the importance of equitable systems for students and families across racial communities in light of the negative impacts of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that we did not capture the mechanisms through which the intervention influenced students’ achievement. For example, multiculturalism could have improved grades by reducing URM students’ stress during the college transition (Levine et al, 2019; Levy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that our findings remained significant after controlling for self‐reported experiences of discrimination suggests that all youth, even those who may be less attuned to ethnic‐racial biases and prejudices, benefitted from school cultural socialization practices. In addition, the school racial climate literature has implicitly assumed that reducing discrimination experiences induces positive outcomes among youth of color (Levine, Markus, Austin, Chen, & Miller, 2019). Because our study revealed that school‐based cultural socialization predicted positive ethnic‐racial identities and better academic grades over and above perceived discrimination, schools’ efforts that promote racial diversity should be considered as strength‐based approaches for improving African American youth’s development.…”
Section: Discussionmentioning
confidence: 99%